THE EFFECT OF MIND MAPPING LEARNING MODEL AND CONTEXTUAL TEACHING AND LEARNING (CTL) TO CONCEPT UNDERSTANDING STUDENTS AT SMP NEGERI 1 PULUNG - Dhika Jeviana; Julan Hernadi (EDUPEDIA, 2017)
This research aims to know: (1) the effect of Mind Mapping learning model to the concept understanding students (2) the effect of Contextual Teaching and Learning model to concept understanding students (3) which is better between of Mind Mapping Learning Model and Contextual Teaching and LearningModel to concept understanding students.This research a quasi-experimental research with population covering all seventh grade students of SMP Negeri 1 Pulung that is consisted of five classes. From five classes, classes VIIC and VIIE were randomly choosen as the sample. Then two classes were taken randomly to determine the type of treatment to be given. Class VIIC was taught by using the Mind Mapping Learning Model and class VIIE was taught by Contextual Teaching and Learning Model. The data collection techniques were a test while the instrument used to collect understanding concept test.The data collection techniques to know is there any understanding concept students is given of treatment Mind Mapping Learning Model betterthan understanding concept students is given of treatment Contextual Teaching and Learning Model  by t-test.The result show that at the significance level of 0.05, concept understanding students more taught by using the Mind Mapping Learning Model was better  than Contextual Teaching and Learning Model.